Vorstellungsrealitäten : Lore Bert - Daniel Buren - Heinz Gappmayr - Joseph Kosuth - Fabrizio Plessi - Karin Sander - Günther Uecker - Lawrence Weiner. - Bleyl, Matthias; Gappmayr, Heinz; Hapkemeyer, Andreas; van der Koelen, Dorothea; Petzinger, Renate; Uecker, Günther (Mainz : Galerie Dorothea van der Koelen, 1995)
Gappmayr, Heinz ; Buren, Daniel ; Kosuth, Joseph ; Sander, Karin ; Uecker, Günther ; Weiner, Lawrence ; Bert, Lore
Vorstellungsrealitäten, Galerie Dorothea van der Koelen, Mainz-Bretzenheim, 11. Februar bis 24. Mai 1995
boek